Motion – The Available Treatments for Hepatitis C Are Cost Effective: Arguments against the Motion - W Ray Kim (Canadian Journal of Gastroenterology)
Hepatitis C is a prevalent infection in North America. However, the natural history of hepatitis C virus (HCV) infection in the general population is not fully understood. Available cohortbased studies suggest that only a relative minority of patients develop significant liver disease, such as cirrhosis and/or hepatocellular carcinoma. Other studies, mostly conducted based on referral patients with established disease, portray much more serious consequences of HCV infection. Although a substantial improvement has been made in the treatment for HCV, the overall impact of antiviral therapy in altering the natural course of HCV infection remains uncertain. Therapeutic trials involve narrow selection criteria that would exclude the majority of hepatitis C patients in the community, and are conducted in ideal settings that may not be generalizable to the average practice setting. Demographic groups that are at high risk of developing severe liver disease include older male patients who consume alcohol. In contrast, antiviral therapy is more effective in young and female patients and those who do not drink alcohol. Thus, patients who appear to be successfully treated may not be those for whom clearance of the virus would be beneficial. Cost-effectiveness studies published to date have not been able to fully address the complex and heterogeneous matrix of the factors that influence the natural history of HCV infection and treatment response.